„Najbardziej elokwentni z Ojców” a metoda przepowiadania w Kościele przełomu IV i V wieku - Nowaszczuk, Jarosław (Vox Patrum, 2023)
Gregory of Nazianzus and John Chrysostom were recognized by posterity as the greatest preachers of the Church in the East. The purpose of the present article is to show that they differed in the way of preparing the texts of public speeches, which implies the need for a separate approach to their output. Both Fathers wrote at a time when rhetoric was used more for entertainment than for the transmission of knowledge, and sophists, known for their oratory proficiency, were considered corrupt and depraved. Over the course of one generation, this led the Church to reject the rhetorical workshop in favor of a genre that is more accessible in terms of form and language – the homily.